Implementing indirect test of RF circuits without compromising test quality: a practical case study - El Badawi, H.; Azais, F.; Bernard, S.; Comte, M.; Kerzerho, V.; Lefevre, F.; Gorenflot, I. (2020 IEEE Latin-American Test Symposium (LATS), 2020)
Cost reduction is a crucial step in testing AMS/RF circuits, and one way of achieving this is to implement an indirect test strategy. Although this strategy relaxes the requirements on test equipment, it still raises some accuracy concerns, which might compromise the test quality. In this work, we explore the benefit that can be brought by a two-tier adaptive test flow, in which only circuits with a sufficient prediction confidence level are evaluated by the indirect test while others are re-evaluated by specification-based test. A methodology is presented that permits to explore different tradeoffs between test quality and test cost and to make pertinent choices for the efficient implementation of such a test flow. The results are illustrated on a front-end RF circuit designed for WLAN applications and show that substantial test cost reduction can be achieved without compromising the test quality.